Pengembangan CIS-MAKOBA V.2 sebagai Self-Monitoring Ibadah Siswa - Muhammad Rofiul Alim; Leseswi Winda Chinteta Puteri (Jurnal Pendidikan Madrasah, 2023)
The purpose of this study was to develop a website-based student worship self-monitoring application. The application was developed to help students monitor and improve worship independently. This research uses research and development methods with a qualitative approach and quantitative approach. Data collection techniques and tools using questionnaires and observations. Data analysis techniques use qualitative and quantitative analysis. The results of this study explain the development of the CIS-MAKOBA V.2 application as an innovation to increase awareness and self-monitoring of student worship. This study showed feasibility with an average score of 87.25% and can be used for students and teachers.